Analysts' earnings forecasts and technological conditions in the firm's investment environment. Issue 2 (August 2015) - Lambert, David; Matolcsy, Zoltan; Wyatt, Anne
Abstract This paper examines the association between sell-side analysts' short and long-term EPS forecasts, growth rates, and forecast errors, and measures of technological conditions in the firm's industry investment environment. Our contention is analysts' industry knowledge includes an understanding of the technological conditions to which the firms' investments are exposed and how these technological conditions within industries map into future earnings. We predict and find as the horizon lengthens that interactions between technological conditions and current EPS are significantly associated with analysts' EPS and growth forecasts. The long horizon EPS growth results align with Jung, Shane and Yang who suggest analysts' growth forecasts reflect efforts to evaluate the firms' long-run prospects. We also present results for analysts' forecast errors that suggest analysts' technological knowledge is associated with optimistically biased long-term forecasts. Our evidence suggests analysts' industry knowledge includes the implications of technological conditions within industries for firms' future earnings.